Cross-Cultural Comparisons of Folktales: Implications for Teaching English Language and Cultural Awareness - Nazar Hasby; Ahmad Faisal; Misrita Misrita; Novi Anoegrajekti; Lailatul Kodriyah; Neneng Islamiah; Fitra Ramadani (Universitas Negeri Padang, 2025)
This research explored cross-cultural comparisons of three folk tales, Cinderella (Europe), Malin Kundang (Indonesia), and Momotaro (Japan), with a focus on their application in English language teaching. The research aimed to analyze these tales' narrative structures, themes, and moral messages and examine their pedagogical value in fostering cultural awareness and enhancing language proficiency among students. Using a qualitative descriptive approach, the research applied Vladimir Propp's narrative structure theory to analyze the common patterns and functions across the folk tales. The findings revealed that, despite their cultural differences, the stories shared similar narrative frameworks, such as the hero's journey, confrontation with evil, and the restoration of justice. Furthermore, the thematic analysis highlighted universal moral messages, such as the consequences of wrongdoing, the importance of filial duty, and the values of teamwork and courage. This research demonstrated that folk tales were valuable tools for enhancing English language instruction, offering students linguistic skills and a deeper understanding of global cultural values. The implications for teaching suggested that folk tales could improve cross-cultural communication, promote critical thinking, and provide an engaging method for language learning, making them a practical pedagogical resource.